Detection of H3F3A K27M or BRAF V600E in liquid biopsies of brain tumor patients as diagnostic and monitoring biomarker: impact of tumor localization and sampling method - Madlener, Sibylle; Stepien, Natalia; Senfter, Daniel; Mayr, Lisa; Laemmerer, Anna; Hedrich, Cora; Baumgartner, Alicia; Lötsch-Gojo, Daniela; Sterba, Jaroslav; Pokorna, Petra; Kiesel, Barbara; Widhalm, Georg; et al. (Acta neuropathologica, 2025)
Gliomas are the most common brain tumor type in children and adolescents. To date, diagnosis and therapy monitoring for these tumors rely on magnetic resonance imaging (MRI) and histopathological as well as molecular analyses of tumor tissue. Recently, liquid biopsies (LB) have emerged as promising tool for diagnosis and longitudinal tumor assessment potentially allowing for a more precise therapeutic management. However, the optimal strategy for monitoring gliomas by LB remains to be determined. In this study, we analyzed circulating tumor DNA (ctDNA) from 78 liquid biopsies (plasma n = 44, cerebrospinal fluid n = 34 (CSF)) of 35 glioma patients, determining H3F3A K28M (K27M) and BRAF V600E mutation allele frequency using droplet digital PCR (ddPCR). All results were correlated to clinically relevant parameters including diagnostic imaging and CSF aspiration site (ventricular vs lumbar) with respect to tumor localization. Regarding diagnostic accuracy, the calculated sensitivity score in the H3F3A K27M cohort was 84.61% for CSF and 73.68% for plasma. In the BRAF V600E cohort, we determined a sensitivity of 83.3% in plasma and 80% in CSF. The overall specificity was 100%. With respect to the CSF aspiration, the intra-operatively obtained CSF demonstrated 100% detection rate, followed by ventricular CSF obtained via Ommaya Reservoir/shunt puncture (93%) and CSF obtained via lumbar puncture (66%). Notably, this further correlated with the proximity of the CSF site to tumor localization. Longitudinal CSF monitoring demonstrated a good correlation to clinical and radiological disease evolution. Importantly, we show for the first time that monitoring BRAF V600E by ddPCR could serve as treatment response assessment in gliomas. In summary, our observation may inform recommendations with regard to location of CSF aspiration when incorporating LB into future treatment protocols.
Keywords: mutace; dospělí; gliom; Female; dítě; předškolní dítě; Adult; mladý dospělý; ženské pohlaví; Adolescent; nádory mozku; lidé; Liquid Biopsy; Mutation; Glioma; cirkulující nádorová DNA; Proto-Oncogene Proteins B-raf; protoonkogenní proteiny B-Raf; Male; nádorové biomarkery; Child, Preschool; Young Adult; Circulating Tumor DNA; Brain Neoplasms; Biomarkers, Tumor; histony; lidé středního věku; Child; Histones; mužské pohlaví; tekutá biopsie; Middle Aged; mladiství; Humans